Bilingualism and Multilingualism in International Teaching - Xinyi Wang (Journal of Linguistics and Communication Studies, 2023)
The process of world economic integration is dramatically changing the spread and use of human languages, and at the same time has a profound impact on human linguistic diversity. In the last half century or so, bilingual and multilingual education has become an important part of the education system of some countries, and bilingual and multilingual education policies have become a hot topic of concern for all walks of life. In this paper, we take the background of international bilingual and multilingual education as a premise, further explore the laws of bilingual and multilingual education, and sort out and summarize the academic discussions on this topic.